1995
DOI: 10.1002/fld.1650211006
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of vortex shedding around a heated/cooled circular cylinder by the three‐step Taylor‐Galerkin method

Abstract: In this paper the vortex shedding around a heatedkooled circular cylinder is numerically simulated by solving the time-dependent Navier-Stokes and energy equations. A finite element method that is referred to as the three-step Taylor-Galerkin method is used to compute these equations. The attention of this study is directed to the investigation of the effect of buoyancy on the vortex street behind the cylinder at constant Reynolds number. The present paper shows the suppression or generation of the von K5umh v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Several studies on heated cylinder exposed to a vertical upward jet reported the breakdown of vortex shedding and formation of a steady wake by heating the cylinder [28,29]. From the previous literature discussions we found that the first transition from steady axisymmetry to steady non-axisymmetry occurs for Re at 200.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies on heated cylinder exposed to a vertical upward jet reported the breakdown of vortex shedding and formation of a steady wake by heating the cylinder [28,29]. From the previous literature discussions we found that the first transition from steady axisymmetry to steady non-axisymmetry occurs for Re at 200.…”
Section: Introductionmentioning
confidence: 94%
“…In the above studies [9,10,[13][14][15][16][17], every study shows that the strongly cooled wake is different from the weakly cooled wake. However, a common difference in [14][15][16][17] has not been elucidated.…”
Section: Introductionmentioning
confidence: 95%
“…Noto and Nakajima [10] in 1991 showed the transitional flow to the strongly cooled wake. Chang and Sa [14] in 1990 and Hatanaka and Kawamura [15] in 1995 computed the strongly cooled wake and showed that the vortex pitch is constant with increasing jRij, but did not show a flow characterizing the strongly cooled wake. Patnaik et al [16] in 1999 computed the strongly cooled wake, but the computed results by Patnaik et al [16] are affected strongly by the numerical viscosity.…”
Section: Introductionmentioning
confidence: 97%
“…Hatanaka and Kawahara [7] observed that, for a Reynolds number of 100, vortex shedding ceases from a circular cylinder at Ri=0.125. Patnaik et al [4] have reported a critical value of Ri=0.120 for vortex shedding suppression at a similar Reynolds number.…”
Section: Resultsmentioning
confidence: 98%